Cognitive therapy of schizophrenia: a new therapy for the millennium. - Beck, Aaron T.; Rector, Neil A. (American Journal of Psychotherapy)
Part of a special section on psychotherapy at the millennium. The writers examine significant advances that have been made during the 1990s in bringing the principles and therapeutic strategies of cognitive therapy to the treatment of schizophrenia. They explain that in a number of large-scale outcome studies with cognitive therapy for schizophrenia, this type of treatment has been demonstrated to offer significant advances for patients not wholly helped by medications. In addition, they explore the “state of the art” conceptualization and strategies used by cognitive therapists to treat positive and negative symptoms.